2017
DOI: 10.3389/fmicb.2017.01232
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diversity of Field Strains of Brucella abortus Biovar 3 Isolated in West Africa

Abstract: Brucellosis is one of the most widespread bacterial zoonotic diseases in the world, affecting both humans and domestic and wild animals. Identification and biotyping of field strains of Brucella are of key importance for a better knowledge of the epidemiology of brucellosis, for identifying appropriate antigens, for managing disease outbreaks and for setting up efficient preventive and control programmes. Such data are required both at national and regional level to assess potential threats for public health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…B. melitensis is responsible for the vast majority of brucellosis in humans and animals in China [13], but the genetic relatedness of B. melitensis within China and its relationship to strains in other world areas is unknown. Investigation of species and genotype distributions, genetic relatedness, and molecular epidemiology of the main circulating strains is essential for understanding the epidemiology of human brucellosis, managing disease outbreaks and for establishing efficient prevention and control programmes [14].…”
Section: Introductionmentioning
confidence: 99%
“…B. melitensis is responsible for the vast majority of brucellosis in humans and animals in China [13], but the genetic relatedness of B. melitensis within China and its relationship to strains in other world areas is unknown. Investigation of species and genotype distributions, genetic relatedness, and molecular epidemiology of the main circulating strains is essential for understanding the epidemiology of human brucellosis, managing disease outbreaks and for establishing efficient prevention and control programmes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Bovine brucellosis can be diagnosed using a variety of serological tests, which complicates the diagnosis for several reasons. However, there is a restriction to the tests, when the organism is intracellular, the disease enters a chronic stage, and the antibody titers may decrease [21,22]. The goal of the current investigation was to use PCR to identify Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…HGDI analysis of B. abortus bv. 3 from West Africa showed that the highest diversity indices were observed with markers composing panel 2 with three to nine alleles, especially at bruce16, which is known as one of the most variable loci [37]. Betsy J et al reported that, historically, approximately 85% of B. abortus infections in the U.S. were caused by biovar 1, which would result in an HGDI≈0.2 [38].…”
Section: Discussionmentioning
confidence: 99%